2020
DOI: 10.1126/sciadv.abc1463
|View full text |Cite
|
Sign up to set email alerts
|

Mandated Bacillus Calmette-Guérin (BCG) vaccination predicts flattened curves for the spread of COVID-19

Abstract: Bacillus Calmette-Guérin (BCG) vaccination may reduce the risk of a range of infectious diseases, and if so, it could protect against coronavirus disease 2019 (COVID-19). Here, we compared countries that mandated BCG vaccination until at least 2000 with countries that did not. To minimize any systematic effects of reporting biases, we analyzed the rate of the day-by-day increase in both confirmed cases (134 countries) and deaths (135 countries) in the first 30-day period of country-wise outbreaks. The 30-day w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
138
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(146 citation statements)
references
References 40 publications
6
138
2
Order By: Relevance
“…On the other hand, and unlike Tdap and Influenza vaccines (both inactivated vaccines), it has been suggested the potential effect of live attenuated vaccines such as the Bacille Calmette-Guérin (BCG, Mycobacterium bovis vaccine) on reducing SARS-CoV-2 infection, by inducing a trained innate immune response [ 20 , 21 ]; this trained immunity is a non-specific response activated through epigenetic changes in myeloid cells and NK cells that lead to a long-term proinflammatory response and confers cross-protection against other pathogens [ 22 ]. Still, the development and administration of SARS-CoV-2 specific vaccines is crucial for limiting the COVID-19 pandemic [ 23 , 24 , 25 ], while the previous ones could be a complement to SARS-CoV-2 specific vaccines in certain settings until herd immunity is achieved with the latest.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, and unlike Tdap and Influenza vaccines (both inactivated vaccines), it has been suggested the potential effect of live attenuated vaccines such as the Bacille Calmette-Guérin (BCG, Mycobacterium bovis vaccine) on reducing SARS-CoV-2 infection, by inducing a trained innate immune response [ 20 , 21 ]; this trained immunity is a non-specific response activated through epigenetic changes in myeloid cells and NK cells that lead to a long-term proinflammatory response and confers cross-protection against other pathogens [ 22 ]. Still, the development and administration of SARS-CoV-2 specific vaccines is crucial for limiting the COVID-19 pandemic [ 23 , 24 , 25 ], while the previous ones could be a complement to SARS-CoV-2 specific vaccines in certain settings until herd immunity is achieved with the latest.…”
Section: Discussionmentioning
confidence: 99%
“…Miller et al analyzed data of several countries as of March 21, 2020, and found a significant correlation between countries with universal BCG vaccination policy and reduced COVID-19 morbidity and mortality [ 7 ]. Berg et al have published a biweekly updated report since April 2020 analyzing the daily rates of COVID-19 case and death increase, and have shown that countries with mandated BCG vaccination policy consistently exhibit flattened curves (slower increases) [ 6 ]. A recent study by Escobar et al carried out detailed population comparisons, e.g., between former East and West Germany, and have found significant correlation BCG immunization and reduced COVID-19 deaths especially in European countries [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on epidemiological reports identifying fewer confirmed cases of SARS-CoV-2 in countries implementing BCG vaccination, it has been postulated that "trained" immunity induced by BCG adjuvants could confer protection against SARS-CoV-2. [123][124][125][126][127] BCG vaccination has been shown to increase the immunogenicity of influenza virus-based vaccine and reduce acute lower respiratory tract infections in children. 127,128 Across 55 countries, BCG significantly mitigated the spread and severity of the COVID pandemic-19 109 .…”
Section: T Cell Cross -Reactivitymentioning
confidence: 99%